HIGHER EDUCATION IN TOURISM FROM THE PERSPECTIVE OF THE LATVIAN TOURISM INDUSTRY - Veliverronena, Linda; Grīnfelde, Ilze (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Several Latvian higher education organisations provide both academic and professional study programmes in tourism from college up to master level. Frequently educators stress that programme's content corresponds to tourism industry needs; however, tourism representatives describe higher education as reactive to the needs rather than proactive. The aim of the study is to explore tourism labour market needs in Latvia and to analyse the employability of graduates and the quality of higher education from the perspective of tourism sector stakeholders in the state and municipal, non-governmental and private sectors. Interviews with informants from small and medium size organizations were selected as data collection method and data were coded and analysed by using the method of content analysis. Results reveal that cooperation between higher education institutions and the tourism sector is insufficient as education partially responds to the needs of the industry. The industry stakeholders suggest strengthening students` skills in sales, cooperation and networking and creative experience design. A data analysis reveals that personal traits and self-efficacy play a more significant role than formal education in the process of staff recruitment. Tourism educators should engage in closer cooperation with the tourism sector to find out needs proactively, reconsider study methods and use a more hands-on approach – improvement of the supply of education does not demand fundamental study content changes but rather transformation of study methods – assessing the effectiveness of existing methods and introducing novel teaching ways.